Holocausts and Resilience. Healing wounds through writing therapeutic short- stories - Mónica Bruder (Psicodebate, 2015)
The resilience, that began conceptually like the description of the capacity of overcoming traumatic adversities in children of diverse communities, extended soon to the study of other social experiences those who, by diverse factors opportunely investigated, could face, control and leave fortified when crossing adverse experiences. Within these categories we find a numerous of testimonies of those communities which were violently exterminated, holocausts, massacres, genocides, slavery, wars, terrorisms of state and civilians and who, in spite of suffering situations of extreme suffering, could appear again from their ashes and transmit models of recovery and messages of realistic hope, among others, of facing strategies as writing and the therapeutic story. The therapeutic story is writing in 3rd person, in fiction format and that is born from the privacy of the most painful situation lived by a person and that she concludes positively. This concept is validated with some testimonies.